Estudio de mercado de la construcción de vivienda como opción de diversificación de mipymes constructoras en Bogotá (2019)
The object of the research is the analysis of the laws and regulations in force associated with the impacts and needs of the supply and demand of construction projects in housing figures. in the VIS and non-VIS segments. Likewise, the real estate markets and the marketability of supply and demand of housing construction projects under construction in the VIS and non-VIS segments in the city of Bogotá are determined in this study. Finally, some estimates are made in the markets of the VIS and non-VIS construction housing segments from the point of view of the attributes and trends of supply and demand.